2010
DOI: 10.1002/for.1184
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear identification of judgmental forecasts effects at SKU level

Abstract: Prediction of demand is a key component within supply chain management. Improved accuracy in forecasts affects directly all levels of the supply chain, reducing stock costs and increasing customer satisfaction. In many application areas, demand prediction relies on statistical software which provides an initial forecast subsequently modified by the expert's judgment. This paper outlines a new methodology based on State Dependent Parameter (SDP) estimation techniques to identify the non-linear behaviour of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…This offers an informative and good explanation of the good performance of negative adjustments on forecasting accuracy. Previous references found that experts' negative adjustments were more accurate (Fildes et al, 2009;Trapero et al, 2011); here, we provide a feasible explanation why this is so, at least regarding adjustments due to promotional activity. Figure 4 depicts the overall results of the forecasting methods under study considering all the observations irrespective of whether they were promoted or not.…”
Section: Resultssupporting
confidence: 61%
“…This offers an informative and good explanation of the good performance of negative adjustments on forecasting accuracy. Previous references found that experts' negative adjustments were more accurate (Fildes et al, 2009;Trapero et al, 2011); here, we provide a feasible explanation why this is so, at least regarding adjustments due to promotional activity. Figure 4 depicts the overall results of the forecasting methods under study considering all the observations irrespective of whether they were promoted or not.…”
Section: Resultssupporting
confidence: 61%
“…Examples of such instructions range from making lesser adjustments (Fildes and Goodwin, 2007;Franses and Legerstee, 2009), to making smaller-sized adjustments (Franses and Legerstee, 2010) or, in contrast, making larger-sized adjustments (Fildes et al, 2009;Trapero et al, 2010) and making lesser upward adjustments (Franses and Legerstee, 2009;Fildes et al, 2009). We believe that these instructions are all rather vague, hard to measure and to quantify and sometimes even contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, these models are extended by imposing constraints for practical considerations. The constraints do not allow the revised order quantity to exceed an upper limit in the case of positive demand adjustment due to limited fund/storage capacity and to fall under a lower limit in the case of negative demand adjustment in order to maintain a target service level (Jammernegg and Kischka [26], Shi et al [27], Abdel-Malek and Otegbeye [28]). A one-dimensional search algorithm is proposed to find the optimal values of the Lagrangian multipliers required in the constrained optimization problems.…”
Section: Introductionmentioning
confidence: 99%